HUBUNGAN PERILAKU PERSONAL HYGIENE SAAT MENSTRUASI DENGAN KEJADIAN PRURITUS VULVAE PADA SISWI KELAS VIII DI MTS MUSLIMIN TANJUNG WANGI KABUPATEN BANDUNG BARAT TAHUN 2025 - Barbara, Maria Awaldina Dua; Febrianti, Indri (SINERGI : Jurnal Riset Ilmiah, 2025)
Background: Pruritus vulvae is an itching sensation in the vulva area. The causes of pruritus vulvae include infection, irritants, allergies, and poor hygiene practices. As many as 30% of female students complain of itching in the vulvae area during menstruation, mostly in grade VIII. The school has not yet made any direct efforts to address the incidence of pruritus vulvae during menstruation. Research Objective: To determine the relationship between personal hygiene behavior during menstruation and the incidence of pruritus vulvae in grade VIII female students at MTS Muslimin Tanjung Wangi, West Bandung Regency in 2025. Research Method: This study used a descriptive observational study with a cross-sectional design. A total sampling technique was used for 41 female students. The research instrument used a questionnaire taken from a previous study. Research Results: The majority of respondents fell into the category of poor personal hygiene behavior, experiencing pruritus vulvae. The chi-square test results obtained p = 0.001. Conclusion: There is a significant relationship between personal hygiene during menstruation and the incidence of pruritus vulvae in eighth grade female students at MTS Muslimin Tanjung Wangi, West Bandung Regency in 2025.